2021
DOI: 10.1007/s10641-021-01073-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificially increased habitat complexity reduces predation-induced mortality for juvenile salmon in simplified environments

Abstract: Many river systems have been artificially modified for various reasons worldwide. Although simplified riverbeds due to artificial modifications often alter the species compositions and interactions, methods for mitigating habitat degradation in such rivers are underdeveloped. In this study, we evaluated the effects of tree branches on the survival of juvenile masu salmon Oncorhynchus masou under predation risk by piscivorous fish (White-spotted charr Salvelinus leucomaenis) in artificially simplified environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…To use binominal distribution to evaluate the effects on mark quality, its four categories were integrated into two, wherein mark qualities of 1 (invisible) and 2 (faintly visible) were classified as unusable (1) and 3 (visible) and 4 (visible brightly) were classified as usable (2). The model was designed with reference to Sahashi and Morita (2017) and Miyamoto et al (2021), and it goes as follows: logit (p) = a1 + b1 Concentration + c1 Immersion time + d1 (b1 Concentration × c1 Immersion time), with p = probability of survival or mark quality; a1 = regression constant; and b1, c1, and d1 = regression coefficients. To determine which of the four hypotheses that were mentioned in the introduction were relevant for this COCHINEAL DYE MARKING OF JAPANESE SMELT study-namely, how concentration and immersion time contribute to mark quality and survival-the dredge function from the MuMIn package, R (version 3.4.3) was used to test all possible combinations of the variables, including their interaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To use binominal distribution to evaluate the effects on mark quality, its four categories were integrated into two, wherein mark qualities of 1 (invisible) and 2 (faintly visible) were classified as unusable (1) and 3 (visible) and 4 (visible brightly) were classified as usable (2). The model was designed with reference to Sahashi and Morita (2017) and Miyamoto et al (2021), and it goes as follows: logit (p) = a1 + b1 Concentration + c1 Immersion time + d1 (b1 Concentration × c1 Immersion time), with p = probability of survival or mark quality; a1 = regression constant; and b1, c1, and d1 = regression coefficients. To determine which of the four hypotheses that were mentioned in the introduction were relevant for this COCHINEAL DYE MARKING OF JAPANESE SMELT study-namely, how concentration and immersion time contribute to mark quality and survival-the dredge function from the MuMIn package, R (version 3.4.3) was used to test all possible combinations of the variables, including their interaction.…”
Section: Methodsmentioning
confidence: 99%
“…The model was designed with reference to Sahashi and Morita (2017) and Miyamoto et al. (2021), and it goes as follows: logit ( p ) = a 1 + b 1 Concentration + c 1 Immersion time + d 1 ( b 1 Concentration × c 1 Immersion time), with p = probability of survival or mark quality; a 1 = regression constant; and b 1, c 1, and d 1 = regression coefficients. To determine which of the four hypotheses that were mentioned in the introduction were relevant for this study—namely, how concentration and immersion time contribute to mark quality and survival—the dredge function from the MuMIn package, R (version 3.4.3) was used to test all possible combinations of the variables, including their interaction.…”
Section: Methodsmentioning
confidence: 99%
“…For juvenile Atlantic salmon, refuge in gravel interstitia, undercut banks and woody debris is important and thought to limit predation risk and restoration efforts have shown that remediating these habitat features can increase juvenile densities (Pulg et al 2022). Direct tests have demonstrated that increased habitat complexity reduced predation (Miyamoto et al 2021). However, mechanistic data to support restoration actions are often more difficult to obtain.…”
Section: Addressing Major Ecological Questions With Predator–prey Tag...mentioning
confidence: 99%